2016
DOI: 10.1002/14651858.cd006103.pub7
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine receptor partial agonists for smoking cessation

Abstract: Analysis 7.2. Comparison 7 Variations in usage, Outcome 2 Non-standard dose varenicline versus placebo at 52 weeks. Analysis 7.3. Comparison 7 Variations in usage, Outcome 3 Standard dose varenicline versus low dose at 52 weeks.. Analysis 7.4. Comparison 7 Variations in usage, Outcome 4 Standard dose varenicline versus high dose at 12 weeks. .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
194
0
25

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(226 citation statements)
references
References 213 publications
7
194
0
25
Order By: Relevance
“…Similarly, buproprion, an anti-depressant, and nicotine replacement therapy via a patch or gum have been shown to be more efficacious in promoting abstinence compared to placebo treatment [60]. A Cochrane systematic review suggested that personalized weight support and counseling may successfully reduce post-cessation weight gain.…”
Section: Smoking Cessation and Glucose Homeostasismentioning
confidence: 99%
“…Similarly, buproprion, an anti-depressant, and nicotine replacement therapy via a patch or gum have been shown to be more efficacious in promoting abstinence compared to placebo treatment [60]. A Cochrane systematic review suggested that personalized weight support and counseling may successfully reduce post-cessation weight gain.…”
Section: Smoking Cessation and Glucose Homeostasismentioning
confidence: 99%
“…The latter serves as a partial agonist at these receptors, acting as a weak agonist in the absence of nicotine, and as a partial antagonist in the presence of nicotine 17 . While the in vitro receptor binding mechanisms of these drugs and their efficacy at a clinical level is established [18][19][20] , it is less clear how their systemslevel neurobiological mechanisms affect the cognitive and affective deficits seen in the human NWS.…”
Section: Introductionmentioning
confidence: 99%
“…Nicotine use via tobacco products accounts for over 5 million deaths annually and billions of dollars in economic cost to society (World Health Organization, 2008). Though several pharmacotherapies have been FDA-approved for the management of nicotine use disorder (e.g., varenicline, bupropion, nicotine replacement therapy (NRT)), these medications are not effective for all smoking populations (Dhelaria et al, 2012; Hajek et al, 2009) and new medication approaches with novel mechanisms of action are urgently needed (Cahill et al, 2016; Yilmazel Ucar et al, 2014 for review).…”
Section: Introductionmentioning
confidence: 99%